Shocks to Philippine households Incidence, idiosyncrasy and impact. - Capuno, J. J.
With their country located in the Pacific Ring of Fire and in the monsoon belt, Philippine households are perennially exposed to natural disasters and calamities. In addition, they face health, economic and sociopolitical risks. Using a nationally representative sample of households, we assess the overall incidence of different shocks, the extent to which they simultaneously affect households in the same area, and their impact. A huge majority of households experience shocks, with the incidence of different shocks being roughly the same for poor and rich households. Natural and economic shocks appear to affect more households simultaneously in the same area than sociopolitical shocks, health shocks and deaths. Health shocks and deaths lead to greater short-term and long-term impacts. Richer households are able to recover better than the poor. We draw some implications for the design and targeting of social health insurance, disaster management and other social protection programs.
Keywords: Economics-Periodicals.; Household shocks; Coping mechanisms; Welfare